Identified support needs for intimate partner violence engagement in an alcohol and other drug treatment sample. (2nd November 2021) - Curtis, Ashlee; Booth, Bridgette; Gruenert, Stefan; Long, Caroline M.; Karantzas, Gery; Harries, Travis; Mullins, Ellie; Miller, Peter G.
ABSTRACT: Background : A high proportion of individuals seeking treatment for alcohol and other drug (AOD) use report engaging in Intimate Partner Violence (IPV). Interventions to reduce IPV, particularly in the context of AOD use, are generally low in effectiveness. Co-design and consumer input enhance ecological validity and attendance rates yet are not common practice. This study aims to gain an understanding of the relationship between AOD use and IPV for those seeking AOD treatment in the Australian treatment system, and to report their treatment needs and perceptions on program design and delivery. Methods : Semi-structured in-depth interviews were conducted with residents in AOD residential rehabilitation services in Victoria, Australia and analyzed using thematic analysis. Results : Nine males identified two themes related to IPV; the anger, guilt and shame experienced, and the role of AOD use. Treatment needs were focussed on communication and emotion regulation skill building. Conclusions : Participants identified their need for skills in managing relationship difficulties. A greater emphasis on these in treatment programs appears to be a useful step for both AOD treatment and IPV interventions.